Semiconductor superlattice zone diagram formation (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2015)
Inroduction. In this paper the input impedance characteristics of unlimited and limited superlattices structures were investigated. Superlattices structures are periodic nanoscale multilayer structures in which a periodic potential of the crystal spatially additionally lattice modulated with potential of this structure.Superlattices’ impedance model. The expressions for input impedance on the left bound of unlimited crystal structure barrier were formed.Impedance characteristics of unlimited superlattices. The input impedance characteristics of unlimited structures were formed. The band nature of the superlattices’ structures through the dependence of active component of input impedance was shown.Impedance characteristics of limited superlattices. By the intercomparison of the reflection coefficient of the limited superlattices and active component of the input impedance of unlimited superlattices was analyzed the formation of the unlimited superlattices’ band diagram. As the result of the analysis of the parameters’ of the forbidden zones of limited superlattices and the number of superlattices’ barriers dependence was analyzed the degree of the parameters’ approximation of the limited superlattices’ band diagrams to the parameters of unlimited superlattice’s band diagram. Three points of matching were found. One point was located in the forbidden zone. The matching condition for the second and the third points meets resonance over-barrier passage of electrons through superlattices.Conclusions. They were found matching conditions of limited superlattices with the environment on their input as well as the features of the formation of the band diagram of superlattices.